2011
DOI: 10.1007/s00397-011-0570-1
|View full text |Cite
|
Sign up to set email alerts
|

Suspension-like hardening behavior of HDPE and time-hardening superposition

Abstract: The rheology of solidifying high-density polyethylene (HDPE) is investigated. Experiments on an HDPE were performed with a novel RheoDSC device. Results agree quantitatively with simulations for a suspension of elastic spheres in a viscoelastic matrix except for very low values of space filling (<5%), indicating that the rheological behavior of the crystallizing melt in the frequency range investigated is purely suspension like. The hardening behavior of the material is characterized in two different ways; a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…Zuidema et al (2001) introduced the above as a necessary addition to the core of the model, which is the coupling between chain stretch and nucleation. Although such a phenomenon would be very hard to measure experimentally, there are clear indications for changes in the rheology of a crystallizing melt during the early stages of crystallization, even when the spherulites are still too small to have a noticeable effect on the viscosity, if the behavior of the material is purely suspension-like [Bove and Nobile (2002) ;Carrot et al (1993); Roozemond et al (2012)]. It is obvious that the nuclei do not create the junction points in a percolating network because they are too far apart (with radius of gyration of chains R g ¼ 10-100 nm and distance between spherulites 10-100 lm), but the mechanism for slowing down of chains involved in nuclei can be of a different nature.…”
Section: B Self-enhancing Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Zuidema et al (2001) introduced the above as a necessary addition to the core of the model, which is the coupling between chain stretch and nucleation. Although such a phenomenon would be very hard to measure experimentally, there are clear indications for changes in the rheology of a crystallizing melt during the early stages of crystallization, even when the spherulites are still too small to have a noticeable effect on the viscosity, if the behavior of the material is purely suspension-like [Bove and Nobile (2002) ;Carrot et al (1993); Roozemond et al (2012)]. It is obvious that the nuclei do not create the junction points in a percolating network because they are too far apart (with radius of gyration of chains R g ¼ 10-100 nm and distance between spherulites 10-100 lm), but the mechanism for slowing down of chains involved in nuclei can be of a different nature.…”
Section: B Self-enhancing Effectmentioning
confidence: 99%
“…First, the reptation and Rouse time of the hmw tail increases as described above. Second, the material can be viewed as a suspension of soft particles (the growing spherulites) in a viscoelastic matrix (the amorphous melt) [Roozemond et al (2012); Steenbakkers and Peters (2008)]. As the spherulites grow, the viscosity of the material increases.…”
Section: Continuous Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, a rheometer can be used to apply flow and monitor subsequent crystallization in terms of rheology [32][33][34][35][36][37][38]. Using a model for the crystallinity dependence of rheological properties [39,40], it is even possible to extract nucleation density from rheological data [25,35]. The evolution of rheological properties with flow-induced structure formation may also play a complex role when strong flows are concerned; it has been observed that the amount of flow-induced structure saturates at a certain level, presumably as a result of decreasing deformation rate caused by increasing viscosity [41,42].…”
Section: State Of the Artmentioning
confidence: 99%
“…(Housmans et al 2009;Vleeshouwers and Meijer 1996), or using continuous shear (Acierno et al 2008;Hadinata et al 2005). It has even been shown that using an appropriate model to link rheological properties and crystalline structure (Steenbakkers and Peters 2008;Roozemond et al 2012), one can extract nucleation density after short-term shear from such experiments (Housmans et al 2009;Ma et al 2011), thus providing an alternative for studies with in situ optical microscopy.…”
Section: Introductionmentioning
confidence: 99%